A Clinical Study Of Post Operative Refraction In Pciol Patients (International Journal of Scientific Research and Management (IJSRM), 2015)
Contract is the cause of preventable blindness worldwide,with the developing world around three quarters of this blindness.One of the routinely done surgery in ophthalmic faculty is cataract operation. The purpose of cataract extraction with PC IOL (posterior chamber intra ocular lens) implantation is to restore the patient’s vision as much and as fast as possible. Such visual rehabilitation involves the correction of significant preoperative astigmatism and refractive error and the avoidance of post operative astigmatism, which may make the prescription of post operative glasses very difficult and even binocular vision impossible